Altered neural processing of emotional faces in remitted Cushing's disease. (September 2015) - Bas-Hoogendam, Janna Marie; Andela, Cornelie D.; van der Werff, Steven J.A.; Pannekoek, J. Nienke; van Steenbergen, Henk; Meijer, Onno C.; van Buchem, Mark A.; Rombouts, Serge A.R.B.; van der Mast, Roos C.; Biermasz, Nienke R.; van der Wee, Nic J.A.; Pereira, Alberto M.
Highlights: Long-term remission of Cushing's disease (CD) still leaves psychological complaints. We investigated processing of emotional faces in remitted CD-patients using fMRI. CD-patients ( n  = 21) showed hypoactivation of the vmPFC relative to controls ( n  = 21). Functional coupling of vmPFC with posterior cingulate cortex was decreased in CD. We report functional brain alterations after cure of endogenous hypercortisolism. Summary: Patients with long-term remission of Cushing's disease (CD) demonstrate residual psychological complaints. At present, it is not known how previous exposure to hypercortisolism affects psychological functioning in the long-term. Earlier magnetic resonance imaging (MRI) studies demonstrated abnormalities of brain structure and resting-state connectivity in patients with long-term remission of CD, but no data are available on functional alterations in the brain during the performance of emotional or cognitive tasks in these patients. We performed a cross-sectional functional MRI study, investigating brain activation during emotion processing in patients with long-term remission of CD. Processing of emotional faces versus a non-emotional control condition was examined in 21 patients and 21 matched healthy controls. Analyses focused on activation and connectivity of two a priori determined regions of interest: the amygdala and the medial prefrontal–orbitofrontal cortex (mPFC–OFC). We also assessed psychological functioning, cognitive failure, and clinical disease severity. Patients showed less mPFC activation during processing of emotional faces compared to controls, whereas no differences were found in amygdala activation. An exploratory psychophysiological interaction analysis demonstrated decreased functional coupling between the ventromedial PFC and posterior cingulate cortex (a region structurally connected to the PFC) in CD-patients. The present study is the first to show alterations in brain function and task-related functional coupling in patients with long-term remission of CD relative to matched healthy controls. These alterations may, together with abnormalities in brain structure, be related to the persisting psychological morbidity in patients with CD after long-term remission.